2008
DOI: 10.1590/s0100-40422008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Tabernaemontana catharinensis root bark: a brief NMR review of indole alkaloids and in vitro cytotoxicity

Abstract: -903 Ribeirão Preto -SP, BrasilRecebido em 1/9/06; aceito em 25/5/07; publicado na web em 3/12/07This work describes the isolation and structural determination of pharmacological compounds present in the bark of roots of Tabernaemontana catharinensis (Apocynaceae). Among the 27 substances detected 12 were identified as terpenoid-indole alkaloids, 2 steroids and 13 pentacyclic triterpenes. Structures were outlined based on HMQC, COSY, DEPT, 13 C, and 1 H NMR data and MS. Spectral data of indole alkaloids were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 19 publications
5
38
0
4
Order By: Relevance
“…A elucidação estrutural dos alcaloides 1-9 envolveu também a comparação com dados de literatura (Figueiredo, 2005;Monnerat, 2005b;Pereira et al, 2008;Souza, 2006). (26), 382 (100), 323 (35), 309 (15), 259 (28), 227 (43), 184 (61), 169 (31), 152 (34), 124 (31).…”
Section: Identificação Dos Alcaloidesunclassified
“…A elucidação estrutural dos alcaloides 1-9 envolveu também a comparação com dados de literatura (Figueiredo, 2005;Monnerat, 2005b;Pereira et al, 2008;Souza, 2006). (26), 382 (100), 323 (35), 309 (15), 259 (28), 227 (43), 184 (61), 169 (31), 152 (34), 124 (31).…”
Section: Identificação Dos Alcaloidesunclassified
“…DC., Apocynaceae, (Syns. Peschiera catharinensis A. DC) has also been denoted as Tabernaemontana affins, Tabernaemontana australis and Tabernaemontana hilariana (Rates et al 1993, Soares et al 2007, and can be found in Argentina, Paraguay, Brazil and Bolivia (Leeuwenberg 1994, Pereira et al 2008. Popularly it is known as "jasmin" (jasmine), "leiteira de dois irmãos" (milkweed) and "cascade-cobra" (snake skin) (Pereira et al 2005, Rates et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Dutta and Ray, 1972;Stevens et al, 1994a;b;van Bergen et al, 1997;Vilegas et al, 1997;Wada et al, 1998;Pereira et al, 2008). Multiflorenyl acetate was found in Cirsium sp.…”
Section: Distribution Of Triterpenyl Acetates In Plantsmentioning
confidence: 95%
“…Jewers and Manchada, 1970;Dutta and Ray, 1972;Woldu et al, 1988;Yoshizumi et al, 1998;Medeiros et al, 2001;Gasparetto et al, 2010). Taraxasteryl and -taraxasteryl acetates were overwhelmingly detected in Asteraceae, with 153 and 29 occurrences, respectively (Dutta and Ray, 1972;Madrigal et al, 1975;Jordon-Thaden and Louda, 2003;Jakupovic et al, 2011), and also in a few Apocynaceae (6 and 2 occurrences, respectively; Jewers and Manchada, 1970;Thakur et al, 1984;Abbott et al, 1990;Sen et al, 1992;Medeiros et al, 2001;Zhang et al, 2006;Yin et al, 2007;Pereira et al, 2008). Bauerenyl acetate was found in three Asteraceae spp., four Apocynaceae and Euphorbia chrysocoma (Cava et al, 1967;Cicció-Alberti and Hoet, 1981;Lao et al, 1983;Shi et al, 2005;Pereira et al, 2008;Jakupovic et al, 2011).…”
Section: Distribution Of Triterpenyl Acetates In Plantsmentioning
confidence: 99%